2015
DOI: 10.1007/s00296-015-3351-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe Jaccoud’s arthropathy in systemic lupus erythematosus

Abstract: Jaccoud's arthropathy (JA) is a clinical situation nowadays present mostly in systemic lupus erythematosus (SLE). It is characterized by the presence of joint deformities such as "swan neck," ulnar deviation and "Z-thumb" resembling rheumatoid arthritis (RA) but that are passively correctable and without bone erosion on plain radiographs. From our cohort of SLE patients with JA, we selected a subgroup with a more severe form of this arthropathy and looked at their clinical and laboratory profile as well as stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Our report confirmed that although bone erosion can be detected more accurately using ultrasound and MRI than with radiography, there are still some patients with JA that show no bone erosion. In addition to our report, there have been several studies describing JA patients without bone erosion based on MRI findings 16–19 . This may indicate that joint deformities with or without bone erosion are two different types of diseases.…”
Section: Discussionsupporting
confidence: 66%
“…Our report confirmed that although bone erosion can be detected more accurately using ultrasound and MRI than with radiography, there are still some patients with JA that show no bone erosion. In addition to our report, there have been several studies describing JA patients without bone erosion based on MRI findings 16–19 . This may indicate that joint deformities with or without bone erosion are two different types of diseases.…”
Section: Discussionsupporting
confidence: 66%
“…However, the spectrum of deformity in JA is very wide, varying from a simple 'reducible' ulnar deviation to a more complicated 'severe' or 'mutilans-type' deformity with fixed joints and subluxations. 6 Thus, a modified set of criteria for JA in SLE contemplating 'severe' forms of the disease has been recently published. 31 The importance of having classification criteria for JA lies in two points: a) standardize patients for future clinical trials; b) distinguish SLE cases with JA from those with RA, as the therapeutic approach is different.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…This is probably secondary to soft tissue fibrosis, disuse of the involved joints and muscle hypotrophy. 6 Curiously, based on Bywaters' report in 1950, the original patient described by Jaccoud was probably an example of the severe form of this arthropathy in whom 'deformity of the hands developed for the first time in the third month of the fifth attack and was initially correctable, only later becoming permanent'. 20 Other authors have confirmed the changing character of the deformities from reducible to fixed.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Although a 'reducible' pattern of arthropathy is observed in the majority of JA cases, in most advanced cases, the joints may become fixed, sometimes referred as to 'severe JA', 2 which is clinically difficult to distinguish from RA. In such situations, misdiagnosis is common, with dangerous consequences.…”
mentioning
confidence: 99%